FRANTIŠEK WEYR (1879-1951). ZAPOMNIANY NORMATYWISTA - Lewandowski, Bartosz (Zeszyty Prawnicze, 2016)
FRANTIŠEK WEYR (1879-1951): A FORGOTTEN NORMATIVIST Summary František Weyr (1879-1951) was one of the most outstanding adherents of the normative theory of legal science during the inter-war period. His scholarly activity was focused on the basic issues important for normativism, on which he embarked shortly before Hans Kelsen’s, and with no influence from Kelsen (Weyr published his earliest book in 1908). Weyr was one of the founders and the main representative of the Czechoslovak Neo-Kantian Law School, which was composed of his former students, members of the Faculty of Law at the Tomáš Masaryk University in Brno. Members of the Czechoslovak Neo-Kantian Law School engaged in numerous polemics on key normativist issues (e.g. the nature of legal norms). F. Weyr’s work in the philosophy of law made a salient contribution to the turbulent history of Czechoslovakia, exerting an influence from the auspicious years of the independent Second Republic (1918-1938), through the period of the Czech and Moravian Protectorate under Nazi German occupation during the Second World War, to the postwar period under the Communist regime and its miserable demise in 1990. Weyr is appreciated in Czech scholarship for his achievements in the theory of law. Although he was one of the key figures associated with normativism, often compared with his colleague H. Kelsen, his work in scholarship is not well known in the Polish theory of law.